Ion-induced surface reactions and deposition from Pt(CO)2Cl2 and Pt(CO)2Br2 - Mohammed K. Abdel-Rahman; Patrick M. Eckhert; Atul Chaudhary; Johnathon M. Johnson; Jo-Chi Yu; Lisa McElwee-White; D. Howard Fairbrother (Beilstein Journal of Nanotechnology)
Ion beam-induced deposition (IBID) using Pt(CO)2Cl2 and Pt(CO)2Br2 as precursors has been studied with ultrahigh-vacuum (UHV) surface science techniques to provide insights into the elementary reaction steps involved in deposition, complemented by analysis of deposits formed under steady-state conditions. X-ray photoelectron spectroscopy (XPS) and mass spectrometry data from monolayer thick films of Pt(CO)2Cl2 and Pt(CO)2Br2 exposed to 3 keV Ar+, He+, and H2+ ions indicate that deposition is initiated by the desorption of both CO ligands, a process ascribed to momentum transfer from the incident ion to adsorbed precursor molecules. This precursor decomposition step is accompanied by a decrease in the oxidation state of the Pt(II) atoms and, in IBID, represents the elementary reaction step that converts the molecular precursor into an involatile PtX2 species. Upon further ion irradiation these PtCl2 or PtBr2 species experience ion-induced sputtering. The difference between halogen and Pt sputter rates leads to a critical ion dose at which only Pt remains in the film. A comparison of the different ion/precursor combinations studied revealed that this sequence of elementary reaction steps is invariant, although the rates of CO desorption and subsequent physical sputtering were greatest for the heaviest (Ar+) ions. The ability of IBID to produce pure Pt films was confirmed by AES and XPS analysis of thin film deposits created by Ar+/Pt(CO)2Cl2, demonstrating the ability of data acquired from fundamental UHV surface science studies to provide insights that can be used to better understand the interactions between ions and precursors during IBID from inorganic precursors.